2013
DOI: 10.2174/15672050113109990155
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Etiology of Alzheimer’s disease: From Genetic to Non- Genetic Factors

Abstract: At present, the etiology of Alzheimer's disease (AD) is still unclear, but both genetic and non-genetic factors are thought to take part in the etiopathogenesis of AD. Epidemiologic researches revealed that genetic factors played a decisive role in the development of both early-onset AD (EOAD) and late-onset AD (LOAD). The mutations in APP, PSEN1 and PSEN2 are inherited in a Mendelian fashion and directly lead to the EOAD, while recent genome-wide association studies have identified numbers of risky genes, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
111
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 180 publications
(117 citation statements)
references
References 207 publications
1
111
0
5
Order By: Relevance
“…The pathogenesis of AD remains unclear and may likely be attributed to the combined effects of numerous factors, such as hereditary, environment, lifestyle, metabolic disturbance, and brain trauma (Querfurth and Laferla 2010;Jiang et al 2013). However, aging is a significant risk factor for the onset of AD (Ballard et al 2011;Bernick et al 2012;Langbaum et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of AD remains unclear and may likely be attributed to the combined effects of numerous factors, such as hereditary, environment, lifestyle, metabolic disturbance, and brain trauma (Querfurth and Laferla 2010;Jiang et al 2013). However, aging is a significant risk factor for the onset of AD (Ballard et al 2011;Bernick et al 2012;Langbaum et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As the most common neurodegenerative disorder in humans, Alzheimer's disease (AD) is characterized by the formation of extracellular amyloid plaques containing aggregated amyloid-β (Aβ) peptides, which is believed to play an important role in the pathogenesis of this disease [1,2]. Accumulating pieces of evidence have indicated that microglia activation induced by Aβ is a "double-edged sword" event in AD.…”
Section: Introductionmentioning
confidence: 99%
“…AD has been classified into two major forms: the early-onset type (<65 years of age) and late-onset type (LOAD; >65 years of age). Its etiology and trajectory can be characterized as a complex interaction effect between environmental and genetic factors [1][2][3][4]. For the genetic realm specifically, mutations in multiple loci have been associated with risk of developing AD of two forms.…”
Section: Introductionmentioning
confidence: 99%